2014
DOI: 10.1002/ejoc.201403385
|View full text |Cite
|
Sign up to set email alerts
|

Selective Formation of Trimethylene Carbonate (TMC): Atmospheric Pressure Carbon Dioxide Utilization

Abstract: Carbon dioxide utilisation (CDU) is currently gaining increased interest due to the abundance of CO2 and its possible application as a C1 building block. We herein report the first example of atmospheric pressure carbon dioxide incorporation into oxetane to selectively form trimethylene carbonate (TMC), which is a significant challenge as TMC is thermodynamically less favoured than its corresponding co-polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 48 publications
1
10
1
Order By: Relevance
“…In each case good yields of the corresponding hydrocarboxylated all‐carbon quaternary center products were observed, again requiring no chromatography during isolation. Interestingly we observed a mixture of products from the reaction of 1 ac , with ring expansion also taking place to afford 2 ac′ , initially we thought this may arise through a similar ring expansion of oxetanes reported by us utilizing a magnesium sacrificial electrode and Bu 4 NI, [14] however on replacement of the Et 4 NI with LiBF 4 we still observed ring opening (although in a 1:1 ratio). We did not observe any ring expansion for the corresponding 1 ab substrate, perhaps indicating that steric hindrance around the oxetane prevents this from occurring.…”
Section: Resultssupporting
confidence: 73%
“…In each case good yields of the corresponding hydrocarboxylated all‐carbon quaternary center products were observed, again requiring no chromatography during isolation. Interestingly we observed a mixture of products from the reaction of 1 ac , with ring expansion also taking place to afford 2 ac′ , initially we thought this may arise through a similar ring expansion of oxetanes reported by us utilizing a magnesium sacrificial electrode and Bu 4 NI, [14] however on replacement of the Et 4 NI with LiBF 4 we still observed ring opening (although in a 1:1 ratio). We did not observe any ring expansion for the corresponding 1 ab substrate, perhaps indicating that steric hindrance around the oxetane prevents this from occurring.…”
Section: Resultssupporting
confidence: 73%
“…In each case good yields of the corresponding hydrocarboxylated allcarbon quaternary center products were observed, again requiring no chromatography during isolation. Interestingly we observed am ixture of products from the reaction of 1ac, with ring expansion also taking place to afford 2ac' ',i nitially we thought this may arise through asimilar ring expansion of oxetanes reported by us utilizing am agnesium sacrificial electrode and Bu 4 NI, [14] however on replacement of the Et 4 NI with LiBF 4 we still observed ring opening (although in a1 :1 ratio). We did not observe any ring expansion for the corresponding 1ab substrate,p erhaps indicating that steric hindrance around the oxetane prevents this from occurring.…”
Section: Methodsmentioning
confidence: 52%
“…A more recent innovation described an electrochemically controlled oxetane/CO 2 coupling process to afford TMC under atmospheric CO 2 pressures. 17 Although metal catalysts have traditionally set benchmark activities for CO 2 -based couplings, organocatalysts are now receiving increased attention and gaining competitiveness. From an initial investigation on the preparation of fivemembered cyclic carbonates (5CCs), 18 we reported that the application of iodine (I 2 ), in combination with organic superbases provides a highly active catalytic system for PTMC synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%